KEDUDUKAN DAN RELASI PERTANGGUNGJAWABAN HUKUM ANTARA ORGANISASI SAYAP PARTAI POLITIK TERHADAP PARTAI POLITIK - Ibnu Sina Chandranegara; Muhammad Ali; Surohmat Surohmat; Andisa Sekarani Wibowo; Muhammad Lutfiadi (FAIRNESS AND JUSTICE, 2020)
In Article 12 point j of Act Number 2 of 2008 concerning Political Parties, a political party has the right to form and have a Political Party Wing Organization.  However, there hasn’t been a further or a specific Political Party Wing Organization regulation both in the elucidation of the Act and the implementation regulations of the Act. This study has the main objective to find the legal status of the Political Party Wing Organization in Indonesia. This research is a normative juridical research. This study concluded that the legal status of the Political Party Wing Organization can be regulated as a public legal entity which is a part of the political party or an independent legal entity. We strongly suggest the regulation of the Political Party Wing Organization must be specified as a chapter in the Political Parties Act or perhaps as a new Act.